Therapeutic hypothermia for stroke: Unique challenges at the bedside - You, Je Sung; Kim, Jong Youl; Yenari, Midori A. (Frontiers in Neurology, 2022)
Therapeutic hypothermia has shown promise as a means of improving neurological outcome from several neurological conditions. At the clinical level, it has been shown to improve outcome in comatose survivors of cardiac arrest and in neonatal hypoxic ischemic encephalopathy. While numerous preclinical studies have shown benefit in stroke models, translating this to the clinical level has proven challenging. Major obstacles include cooling the typical stroke patient who is awake and breathing spontaneously, but often has significant comorbidities. Solutions around these problems include selective brain cooling and cooling to lesser depths or avoiding hyperthermia. This review will cover the mechanisms of protection by therapeutic hypothermia, as well as recent progress made in selective brain cooling and the neuroprotective effects of only slightly lowering brain temperature. Therapeutic hypothermia for stroke has been shown to be feasible, but has yet to be definitively proven effective. There is clearly much work to be done in this area.